A review of hirschsprung's disease in Hospital Universiti Sains Malaysia 1999-2004 - Yahya, Maya Mazuwin (2006)
Introduction Hirschsprung' s disease is a developmental disorder of the enteric nervous system causing congenital megacolon and the commonest cause of intestinal obstruction in the neonatal period. Being the only Pediatric surgical unit until the end of 2005 Hospital USM undertook all the references for Hirschsprung's disease in the upper east coast region of Malaysia. The treatment of the disease started when a patient is suspected of having the disease clinically. The patient would receive rectal irrigation until the diagnosis is confirmed by rectal biopsy. When the diagnosis is confirmed the child would have a colostomy created. When the child reached about one year old or weight of 10 kilograms, the definitive procedure would be done. Until 2004, the procedure of choice in the hospital was Duhamel procedure. After the definitive procedure, the colostomy would be closed. Objective: The objective of the study is to review the children presenting with Hirschsprung's disease to the hospital and described the demographics, mode and age of presentations, diagnosis, operative treatment, complications and outcome of the patients. Methodology: The study was retrospective review study of the patients who were diagnosed and had their definitive pull-through procedure in the hospital during a period of 5 years (from February 1999 - February 2004). Patients who defaulted prior to the definitive procedure were excluded. Results: There were 94 patients whose data was available for the review. There were 4: 1 male to female ratio with age of presentation ranging from I day old and I3 years old with 73.4% presented within the age of 3 months. The most common of clinical presentation was abdominal distension (87.2%) followed by vomiting (61.7%), poor feeding (55.3%), delayed passage of meconium (47.9%) and chronic constipation (46.8%). Seventeen percent (I 7%) of patients had other associated anomalies and 3.2% had a family history. Sixty three percent (63.4%) were diagnosed with rectal suction biopsy. Ninety five percent (95.7%) of patients had Duhamel type of pull-through procedure with 3 had transanal pull-through and only one who had Soave. There was a mortality recorded for the study and it was attributed to enterocolitis. The patient was also having Down syndrome and congenital heart disease. In the follow up period an average of 74% were free of complications of constipation, enterocolitis, incontinent, redo operation. There was I 0.6% reoperation rate. Five patients needed a complete redo of their definitive procedures. Conclusion The demographics finding of the study is quite similar to the patterns in the other parts of the world. The presenting symptoms were also quite similar to other studies. The definitive procedure of choice during the study time was Duhamel operation. The operative outcome was safe and acceptable.